Voices In Language Research (2025)
Voices in Language Research brings together a diverse collection of studies that reflect the evolving concerns and innovations in contemporary language research. Spanning eleven chapters, the volume explores a wide range of themes from corpus linguistics, phoneme awareness, and classroom observation to the challenges of flipped learning and digital pedagogy. It also tackles urgent and sensitive topics such as extremist discourse, disaster reporting, the impact of the COVID-19 pandemic on student motivation, and the role of trauma in second language learning.The book foregrounds the “voices” of researchers, highlighting not only theoretical debates and methodological innovations but also human experiences and challenges that underpin the study of language. By weaving together perspectives from linguistics, education, media studies, and digital communication, the collective voices demonstrate how language research is both intellectually rigorous and deeply connected to real-world contexts.This volume is intended for academics, postgraduate students, educators, and practitioners who wish to engage critically with the complexities of language use, learning, and representation. Voices in Language Research affirms the importance of listening to diverse voices or perspectives in language research while striving to promote inclusivity, ethical standards, and empathy.